2021
DOI: 10.7554/elife.62927
|View full text |Cite
|
Sign up to set email alerts
|

Cancer immunotherapy by NC410, a LAIR-2 Fc protein blocking human LAIR-collagen interaction

Abstract: Collagens are a primary component of the extracellular matrix and are functional ligands for the inhibitory immune receptor leukocyte associated immunoglobulin-like receptor (LAIR)-1. LAIR-2 is a secreted protein that can act as a decoy receptor by binding collagen with higher affinity than LAIR-1. We propose that collagens promote immune evasion by interacting with LAIR-1 expressed on immune cells, and that LAIR-2 releases LAIR-1 mediated immune suppression. Analysis of public human datasets show that collage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 68 publications
2
39
0
Order By: Relevance
“…Here, we have shown that MMP generated collagen fragments cause immunomodulation through LAIR-1, potentially mediating T cell immunosuppression both in the TME and in the circulation. These findings further strengthen LAIR-1 as a promising therapeutic target to improve cancer treatment and overall survival (26,33,37). Previously, we showed that LAIR-2-Fc can revert collagen-induced LAIR-1 mediated immunosuppression, resulting in decreased tumor outgrowth in humanized mouse models (33).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Here, we have shown that MMP generated collagen fragments cause immunomodulation through LAIR-1, potentially mediating T cell immunosuppression both in the TME and in the circulation. These findings further strengthen LAIR-1 as a promising therapeutic target to improve cancer treatment and overall survival (26,33,37). Previously, we showed that LAIR-2-Fc can revert collagen-induced LAIR-1 mediated immunosuppression, resulting in decreased tumor outgrowth in humanized mouse models (33).…”
Section: Discussionsupporting
confidence: 55%
“…These findings further strengthen LAIR-1 as a promising therapeutic target to improve cancer treatment and overall survival (26,33,37). Previously, we showed that LAIR-2-Fc can revert collagen-induced LAIR-1 mediated immunosuppression, resulting in decreased tumor outgrowth in humanized mouse models (33). Therefore, LAIR-2-Fc is currently being evaluated in a clinical trial (NCT04408599).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations